Assessing adolescents with the MACI using the Millon Adolescent Clinical Inventory - McCann, Joseph T (John Wiley & Sons, 1999)
Assessing Adolescents with the MACI is an interpretive guide for using the Millon Adolescent Clinical Inventory Test--the most widely-used personality assessment test for adolescents